Rare bird documentation form for Northern Goshawk near Coralville Dam in 1972 - Halmi, Nicholas S.et al (1972)
Rare bird documentation form for a Northern Goshawk near Coralville Dam in Johnson County, IA on November 17, 1972, January 14, 1973, and January 28, 1973. Contex - flatbed